Thirty Days Snail Biscuit Supplementation Improved Height-for-age Z-score (HAZ) of Malnourished Children in Slum Surabaya - Trias Mahmudiono; Zeni Firginingtyas; Qonita Rachmah (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2017)
Background: Indonesia is now still suffering from malnutrition. It was reported that at least 1.39% out of 136,155 children under-five in Surabaya were severely. Severe malnutrition caused by direct factors including infectious diseases and food intake. Therefore, an alternative to overcome that problem is crucial, such as using snail flour for a weaning food. Snail is known as one of the good protein source with complete essential amino acid.Objective: This research aims to determine the effect of snail biscuit (Achatina fulica) toward z-score improvement in severely malnourished children under five according weight for age and height for age index in Ujung sub-district, Surabaya.Methods: This was an experimental research which divided into two groups; case group that given snail biscuit for a month and control group that given coconut biscuit in a same time period. Paired t-test was done to analyze the different between before and after treatment.Results: The result showed that there was no effect of snail biscuit to weight-for-age z-score (WAZ) improvement in children under five (p-value>0.05). However, a month snail biscuit intervention improved height-for-age z-score (HAZ) in children under five (p-value=0.02); while the control group did not show significant result (p-value=0.84). The strength of intervention shown by Exp(B) value=1.02 means that children under five who consume snail biscuit for a month had 1.02 higher height-for-age z-score improvement compared to those who consumed coconut biscuit.Conclusion: It can be concluded that snail biscuit give better improvement of nutritional status based on height-for-age z-score compared to coconut biscuit in malnourished children under five. It is suggested for the intervention study to expand intervention period to 90 days similar to government supplementary feeding intervention. ABSTRAK Latar belakang: Malnutrisi masih menjadi masalah gizi utama yang dialami di Indonesia. Dinas Kesehatan Kota Surabaya pada tahun 2009 melaporkan sebesar 1,888 (1.39%) dari 136,155 balita mengalami gizi buruk. Penyebab gizi buruk terdiri dari faktor langsung dan tidak langsung, dimana faktor langsung terdiri dari penyakit infeksi dan asupan makanan. Salah satu alternatif yang dapat digunakan adalah penggunaan tepung bekicot sebagai makanan pendamping. Bekicot diketahui sebagai salah satu sumber protein dengan kandungan asam amino esensial yang lengkap.Tujuan: Penelitian ini bertujuan untuk mengetahui efek pemberian biskuit bekicot (Achatina fulica) pada perbaikan z-score berat badan menurut usia dan tinggi badan menurut usia balita gizi buruk di Kelurahan Ujung, Surabaya.Metode: Penelitian ini menggunakan desain studi eksperimental dengan pembagian dua kelompok; kelompok intervensi yang diberikan biskuit bekicot selama 30 hari dan kelompok kontrol yang diberikan biskuit kelapa dalam jangka waktu yang sama. Uji statistik yang digunakan yaitu paired t-test.Hasil: Hasil analisis menunjukkan tidak ada efek pemberian biskuit bekicot selama satu bulan pada indeks status gizi berat badan menurut umur (BB/U) (P-value>0,05). Namun, intervensi pemberian biskuit bekicot secara statistik mempengaruhi perbaikan status gizi tinggi badan menurut usia (TB/U) pada balita gizi buruk, sedangkan biskuit kelapa tidak mempengaruhi TB/U balita gizi buruk (P-value=0.84). Kekuatan pengaruh intervensi berdasarkan perhitungan Exp(B)=1.02, artinya bahwa balita gizi buruk yang mengonsumsi biskuit bekicot memiliki 1.02 kali perbaikan yang lebih baik pada status gizi TB/U dibandingkan balita yang mengonsumsi biskuit kelapa.Kesimpulan: Dapat disimpulkan bahwa biskuit bekicot dapat menjadi alternatif perbaikan status gizi balita gizi buruk. Penelitian selanjutnya disarankan dapat memperpanjang durasi intervensi hingga 90 hari seperti anjuran pemerintah dalam pemberian makan tambahan.